Blaustein's pathology of the female genital tract - Kurman, Robert J; Ellenson, Lora Hedrick; Ronnett, Brigitte M (Springer, 2011)
The publication focuses on the field of gynecologic patology. Intended for the professional public.
Keywords: Genital Diseases, Female; Genitalia, Female; ženské pohlavní orgány; gynekologie a porodnictví; gynekologická onemocnění